THE INFLUENCE OF STUDENTS’ GRAMMAR PROFICIENCY ON READING ABILITIES: A STUDY AT AN ISLAMIC BOARDING SCHOOL - Siti Habsah; Hikmah Pravitasari; Amila Yashila Rahmah; Hasanatie Rahayu Agustina; Nidaul Hasanah; Mia Agustina; Nurul Adhani (English Didactic, 2022)
This study explored the relationship between grammar and reading abilities of third-grade junior high school students of an Islamic boarding school in Indonesia. The total number of students sampled in this study was 60 students, with details consisting of 30 female students and 30 male students. The data collection instruments used in this research were grammar tests and reading comprehension tests. The researchers analyzed the data using Pearson Product Moment Correlation and calculated the data using Microsoft Excel 2019 program to test the hypothesis. The result of calculation using Microsoft Excel 2019 program found that the correlation coefficient of grammar mastery and students' reading ability is 0.93 with a significant level of 0.01. With these results, it can be seen that these variables are positively correlated. And there is a significant relationship between grammar mastery and the student's reading ability.